The Dynamics of Law Enforcement in Indonesia: According to Donald Black's Legal Discrimination Theory - Dwi Rahmawati; Hikmatul Abibah (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2025)
Introduction: This article analyzes the justice crisis of several cases of law enforcement due to legal stratification Donald Black`s Teheory and explains integrative steps to overcome the problem of law enforcement discrimination in Indonesia. Purposes of the Research: This research identifies the dynamics of law enforcement due to the existance of legal stratification Donald Black and factors that legal discrimination. Methods of the Research: Normative research method that conducts library research through varios library materials such as books, academic articles, and official reports related to the object under study. Results Main Findings of the Research: Law enforcement discrimination in Indonesia often occurs based on social stratification. The rich have better access to litigation and are more likely to win legal cases, while the poor have difficulty obtaining justice. This reflects bias within the legal system, which has the potential to hinder the creation of social order and justice. To overcome discrimination in law enforcement must prioritize improvements in three main parts: legal substance, legal structure, and legal culture. These three parts must run synergistically, because weaknesses in one part will weaken the legal system as a whole. Pancasila as the basis of the state must be the main guideline in law formation and enforcement. To achieve a legal unbiased system in Indonesia, a commitmen is needed from lawmakers and law enforcement officials. With a balance between substance, structure, and legal culture, a fair and effective legal system can be achieved.